A method for preparing a high-performance all-solid-state lithium-ion battery
Read the electrolytic film of polymer through the solution, and use the combination of modifiers to remove soil and polymer (partial diofluoroethylene-hexarinylyl) to solve the problem of low-level lithium-ion battery diaphragm ion conductivity, realize High -performance and high -safety ion -ion battery.
Patent Information
- Application Number
- CN202111121492.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-09-24
AI Technical Summary
The separator ion conductivity of existing all-solid-state lithium-ion batteries is low, resulting in poor battery performance and difficulty in achieving large-scale production.
The polymer electrolyte film is used to cast a polymer, which is used to increase the conductivity through methyl acrylic methyl polymerization. Transmission activity site of ions.
The preparation of high-performance all-solid-state lithium-ion batteries has been achieved, with an ionic conductivity reaching 1.1×10-3S cm-1, which has the advantages of high safety and suitability for commercial applications.
Smart Images

Figure CN113839099B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a polymer electrolyte for an all-solid-state lithium-ion battery. Background Art
[0002] Commercial lithium-ion batteries still face safety issues because they contain electrolytes that are prone to fire and leakage hazards. At the same time, the development of traditional liquid lithium-ion batteries has also encountered bottlenecks due to the growth of lithium dendrites. Therefore, flammable electrolytes are the main obstacle that needs to be overcome, and the contradiction between high energy density and high safety needs to be resolved. Therefore, solid-state polymer-based lithium-ion batteries have attracted widespread attention due to their high safety. However, their low ionic conductivity, poor mechanical properties and insufficient cycle life limit their practical applications. Wu et al. selected nickel phosphate (VSB-5) nanorods as fillers and prepared a new polyethylene oxide / LiTFSI / nickel phosphate polymer electrolyte. The ionic conductivity of this polymer electrolyte is as high as 4.83×10 -5 S cm -1 , with an electrochemical stability of up to 4.13 V. The increase in ionic conductivity is attributed to the interaction between nickel phosphate and polyethylene oxide-LiTFSI, which can reduce the crystallinity (Z. Wu, Z. Xie, A. Yoshida, J. Wang, T. Yu, Z. Wang, X. Hao, A. Abudula, G. Guan, J. Colloid Interface Sci. 565 (2020) 110–118.). Xu used a self-assembled polyethylene oxide@silica three-dimensional network structure composite polymer electrolyte. Due to the rigid-flexible coupling structure of strong Lewis acid-base and weak hydrogen bonds, silica nanoparticles are uniformly dispersed into polyethylene oxide, which can significantly reduce the crystallinity of polyethylene oxide, thereby enhancing the ionic conductivity (1.1×10 -4 S cm -1 ) and high interfacial stability between electrolyte and electrode (Z.Xu, T.Yang, X.Chu, H.Su, Z.Wang, N.Chen, B.Gu, H.Zhang, W.Deng, H.Zhang, W. Yang, ACS Appl.Mater.Interfaces 12(2020)10341–10349.). However, solid-state lithium-ion batteries still have problems such as large interfacial impedance, poor battery performance at low temperatures, and low ionic conductivity that need to be solved in order to achieve large-scale production. Summary of the invention
[0003] The purpose of the present invention is to solve the problem of low ion conductivity of all-solid-state lithium-ion battery separators prepared by existing methods, and to provide a method for preparing a high-performance all-solid-state lithium-ion battery.
[0004] The present invention provides a method for preparing a high-performance all-solid-state lithium-ion battery, wherein the method is prepared according to the following steps:
[0005] 1. Pretreatment of polymer electrolyte precursor solution
[0006] Dissolve poly(vinylidene fluoride-hexafluoropropylene) copolymer, polyvinylidene fluoride and organic montmorillonite in a mass ratio of 5:1:1 to 4:3:2 respectively with an organic solvent N,N-dimethylformamide, stir evenly at room temperature, and mix the stirred solutions;
[0007] 2. Preparation of polymer electrolyte precursor monomer
[0008] Add methyl methacrylate: poly(vinylidene fluoride-hexafluoropropylene) copolymer, polyvinylidene fluoride, organic montmorillonite: lithium salt in a mass ratio of 20:1:3 to 35:9:20 to the uniform solution obtained in step 1, and stir at room temperature to obtain a uniform light yellow solution;
[0009] 3. Polymerization of polymer electrolyte precursor monomers
[0010] Add an initiator to the light yellow solution of step 2, and prepolymerize for 10 to 30 minutes under heating conditions to obtain a precursor solution;
[0011] 4. Preparation of polymer electrolyte for all-solid-state lithium-ion batteries
[0012] The precursor solution obtained in step 3 is cast on a glass plate by solution casting, and vacuum dried at 75-95° C. for 2-4 h to obtain a light yellow polymer electrolyte film, which is then sliced for later use after being cooled to room temperature;
[0013] 5. Battery Assembly
[0014] The negative electrode shell, the polymer electrolyte film obtained in step 4, the lithium sheet, the nickel foam and the positive electrode shell are assembled in the order of argon gas in a glove box to obtain the high-performance all-solid-state lithium-ion battery.
[0015] The organic montmorillonite described in step 1 is modified montmorillonite.
[0016] The purpose of the modified montmorillonite is to increase the interlayer spacing of montmorillonite, which is beneficial to the migration of lithium ions between montmorillonite layers, change the hydrophilicity of montmorillonite layers, enhance the dispersibility of montmorillonite in organic solvents, and increase the interface and interfacial energy to form active sites for lithium ion migration. The basic structural unit of montmorillonite is a piece of aluminum oxide octahedron sandwiched between two pieces of silicon oxide tetrahedron, forming a layered structure by sharing oxygen atoms. There is excess negative charge on the surface of these sheets, which will cause the montmorillonite sheets to adsorb cations. The lithium ions in lithium-ion batteries can be adsorbed between the layers. Montmorillonite has a hydrophilic microenvironment that is not conducive to the insertion of lipophilic monomers and polymers. The organic part of the organically modified montmorillonite remains in the interlayer. The modified montmorillonite can increase the interlayer spacing of montmorillonite, change the hydrophilicity of the montmorillonite interlayers to hydrophobicity, enhance the dispersibility of montmorillonite in organic solvents, and build a channel for lithium ion transmission through polymer block-montmorillonite interlayer-polymer block, and increase the interfacial area in the polymer electrolyte, improve the interfacial energy, increase the active sites for lithium ion migration, make lithium ions easy to migrate in the solid electrolyte, thereby improving the conductivity and lithium ion migration number.
[0017] Furthermore, the lithium salt added in step 2 is one of chlorine perchlorate, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium hexafluorophosphate, and lithium hexafluoroarsenate.
[0018] Chlorine perchlorate, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium hexafluorophosphate, and lithium hexafluoroarsenate can continuously replenish consumed lithium ions in the polymer electrolyte due to their high electrochemical stability and conductivity, thus promoting long-term and stable battery circulation.
[0019] Furthermore, after adding the lithium salt in step 2, the stirring time is controlled to be 4 to 8 hours.
[0020] The time control here is to ensure that the lithium salt is completely dissolved and does not precipitate during use. Insufficient stirring time will result in the lithium salt not being fully dissolved, and too long stirring time will result in the lithium salt precipitating.
[0021] Furthermore, the initiator described in step three is one of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, and isophenylpropane hydroperoxide.
[0022] Azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, and isophenylpropane hydroperoxide are unstable molecules and easily form free radicals. The free free radicals can induce the polymerization of methyl methacrylate monomer.
[0023] Furthermore, the mass of the initiator in step three accounts for 0.03-0.06% of the total mass of the light yellow polymer electrolyte mixed in step two, and the prepolymerization temperature is 70-100°C.
[0024] Too low a quality of benzoyl peroxide will result in insufficient degree of polymerization of the methyl methacrylate monomer, making it impossible to form a film during the drying process. Excessive benzoyl peroxide will result in too high a degree of polymerization of the methyl methacrylate monomer, which will solidify during the prepolymerization process and cannot be cast into a film.
[0025] Furthermore, when the polymer electrolyte film is prepared by casting in step 4, it needs to be left to stand and defoam in advance.
[0026] Defoaming in advance can prevent the film from breaking during the drying process. Precursor liquid that has not been defoamed in advance will form large defects at the bubble position during the film-forming process, resulting in experimental failure and waste of drugs.
[0027] The present invention has the following beneficial effects:
[0028] The present invention adopts a solution casting method to prepare an all-solid-state lithium-ion battery separator using three insoluble phases as a matrix, focusing on the influence of polymethyl methacrylate after methyl methacrylate polymerization on the morphology of the polymer electrolyte membrane and the electrochemical performance of the lithium-ion battery, including ionic conductivity, charge and discharge specific capacity, cycle efficiency, and cycle stability. The ionic conductivity of the all-solid-state lithium-ion battery separator prepared by the casting method using methyl methacrylate polymerization as a matrix reaches σ=1.1×10 -3 S cm -1 , opening up a new path for high-performance and high-safety all-solid-state lithium-ion batteries.
[0029] The ionic conductivity of polyvinylidene fluoride is poor, but the molecular chains are closely arranged and have strong hydrogen bonds, and have good toughness. Poly(vinylidene fluoride-hexafluoropropylene) copolymer has high-density pores and good electrochemical stability, but high cost and poor mechanical strength, which can just neutralize the rigidity of polyvinylidene fluoride and keep the polymer electrolyte soft. The methyl methacrylate added in step 2 can not only act as a solubilizer to fully contact and mix with the other two matrixes and fillers, and then perform polymerization treatment of methyl methacrylate, the combination of the three substances can maximize the toughness and mechanical strength of the polymer electrolyte, improve the cycle performance of the battery, prevent lithium dendrites generated during the battery cycle from piercing the diaphragm and causing fire, and increase the safety of the solid polymer electrolyte film.
[0030] Through electrochemical testing, we compared it with similar materials reported so far, and the results are as follows:
[0031] The ionic conductivity and initial discharge specific capacity measured at different temperatures show that the ionic conductivity and initial discharge specific capacity of the all-solid-state polymer electrolyte of the present invention are superior to those of the currently reported polymer electrolytes (ACS Applied Materials & Interfaces, 2018.), (ACS Omega, 2019, 4(1):95-103.), (Chem Electro Chem, 2020, 7(5):1213-1224.), (Carbohydrate Polymers, 2020, 246:116622.), (Journal of the Electrochemical Society, 2007, 154(11):A1048.), (Journal of Materials Science, 2020, 55(26):12249-12263.), (Electrochimica Acta, 2017:752-759.), (Electrochimica Acta, 2018, 286: 242-251.);
[0032] Existing all-solid-state lithium-ion batteries have the problems of low ion conductivity and rapid capacity decay, making them difficult to achieve commercial production. The all-solid-state polymer electrolyte of the present invention, with the help of the layered structure of organic montmorillonite and a large number of Lewis acid centers, can accelerate the dissociation of lithium salts and allow lithium ions to migrate smoothly. The present invention adopts a solution casting method to prepare a polymer electrolyte membrane. Due to the different surface tensions of each substance in the polymer electrolyte, a large number of interfaces are generated, and the modified montmorillonite layered interface has a high specific surface area. The poly(vinylidene fluoride-hexafluoropropylene) copolymer has a low glass transition temperature of -55 degrees, which is much lower than the homopolymer, so that the transfer of lithium ions therein follows the Arrhenius equation and has good electrical conductivity. Due to its high fluidity, it is easy to insert into the montmorillonite layer to form a lithium ion channel of polymer block-modified montmorillonite layer-polymer block. Since polyvinylidene fluoride is a component of the poly(vinylidene fluoride-hexafluoropropylene) copolymer, it is easy to fuse with the poly(vinylidene fluoride-hexafluoropropylene) copolymer, so the modified montmorillonite can be introduced into the poly(vinylidene fluoride-hexafluoropropylene) copolymer. The poly(methyl methacrylate) Ester is the main matrix material for supporting the above materials. It will improve the self-supporting performance of the electrolyte and provide a template for montmorillonite and layer-embedded poly(vinylidene fluoride-hexafluoropropylene) copolymer and polyvinylidene fluoride. Therefore, the modified montmorillonite, poly(vinylidene fluoride-hexafluoropropylene) copolymer, polyvinylidene fluoride and polymethyl methacrylate that wrap montmorillonite and introduce it into the block polymer are compatible with each other to produce multi-folds, multi-porous morphology and multi-dimensional interface that are conducive to lithium ion migration, and build a lithium ion channel for lithium ion transmission through polymer block-montmorillonite interlayer-polymer block, and increase the interface area in the polymer electrolyte, improve the interface energy, and increase the active sites for lithium ion transmission, not only to obtain ultra-high ion conductivity, but also with the advantages of simple and safe operation, suitable for large-scale preparation and commercial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is an infrared spectrum of a polymer electrolyte prepared by a method for preparing a high-performance all-solid-state lithium-ion battery;
[0034] Figure 2 This is a SEM image of a polymer electrolyte prepared by a method for preparing a high-performance all-solid-state lithium-ion battery;
[0035] Figure 3 This is an XRD diagram of a polymer electrolyte prepared by a preparation method for a high-performance all-solid-state lithium-ion battery;
[0036] Figure 4 This is an impedance diagram of a polymer electrolyte prepared by a method for preparing a high-performance all-solid-state lithium-ion battery;
[0037] Figure 5Arrhenius diagram of a polymer electrolyte prepared by a method for preparing a high-performance all-solid-state lithium-ion battery;
[0038] Figure 6 A constant current polarization curve diagram of an all-solid-state lithium-ion battery prepared by a method for preparing a high-performance all-solid-state lithium-ion battery;
[0039] Figure 7 A rate diagram of an all-solid-state lithium-ion battery prepared by a method for preparing a high-performance all-solid-state lithium-ion battery;
[0040] Figure 8 A cyclic voltammetry curve of an all-solid-state lithium-ion battery prepared by a method for preparing a high-performance all-solid-state lithium-ion battery;
[0041] Fig. 9 The specific capacity-voltage curve of the comparative example of the present invention cycled at 0.5C;
[0042] Fig.10 The efficiency-specific capacity curve of the comparative example of the present invention cycled at 0.5C;
[0043] Fig.11 The specific capacity-voltage curve of an all-solid-state lithium-ion battery cycled at 0.5 C prepared by a preparation method of a high-performance all-solid-state lithium-ion battery is shown;
[0044] Fig.12 The figure is a graph showing the efficiency-specific capacity curve of an all-solid-state lithium-ion battery at 0.5 C prepared by a method for preparing a high-performance all-solid-state lithium-ion battery.
[0045] Fig.13 This is a comparison chart of the all-solid-state lithium-ion battery prepared by the preparation method of a high-performance all-solid-state lithium-ion battery in Example 1 through electrochemical testing with similar materials currently reported. DETAILED DESCRIPTION
[0046] The present invention will be further described below in conjunction with the best embodiments, but the protection scope of the present invention is not limited to the following embodiments.
[0047] Experimental drugs
[0048]
[0049] Instrument Name model factory Analytical Balance FC-204 Shanghai Jingke Balance Magnetic stirrer CL-200 Gongyi Yuhua Instrument Co., Ltd. Vacuum Dry Green Box ZK-82BB Shanghai Experimental Instrument Factory Co., Ltd. Japanese style battery sealing machine MSK-110 Shenzhen Kejing Zhida Technology Co., Ltd. Pole punching machine MSK-T10 Shenzhen Kejing Zhida Technology Co., Ltd. LAND Battery Testing System CT2001A Wuhan Jinnuo Electronics Co., Ltd. X-ray traversing instrument X′Pert PRO Panalytical Electrochemical workstation CHI760E Shanghai Chenhua Instrument Co., Ltd. Scanning electron microscopy FEI sisirion200 FEI Vacuum glove box ZKX Nanjing University Instruments Thermogravimetric Analyzer TGA / SDTA 851e Mettler Toledo
[0050] Comparative Example: This comparative example was prepared according to the following steps:
[0051] 1. Pretreatment of polymer electrolyte precursor solution: Poly(vinylidene fluoride-hexafluoropropylene) copolymer, polyvinylidene fluoride and organic montmorillonite in a mass ratio of 5:1:1 to 4:3:2 are dissolved in an organic solvent N,N-dimethylformamide, stirred evenly at room temperature, and the stirred solutions are mixed;
[0052] 2. Preparation of polymer electrolyte precursor monomer
[0053] Add methyl methacrylate: poly(vinylidene fluoride-hexafluoropropylene) copolymer, polyvinylidene fluoride, organic montmorillonite: lithium salt in a mass ratio of 20:1:3 to 35:9:20 to the uniform solution obtained in step 1, and stir at room temperature to obtain a uniform light yellow solution;
[0054] 3. Preparation of polymer electrolyte for all-solid-state lithium-ion batteries
[0055] The uniform viscous solution obtained in step 2 is cast onto a glass plate by solution casting, and vacuum dried at 80-100° C. for 2-4 h to obtain a light yellow polymer electrolyte film, which is then sliced after being cooled to room temperature for later use.
[0056] Example 1: A method for preparing a high-performance all-solid-state lithium-ion battery of this example is prepared according to the following steps:
[0057] 1. Pretreatment of polymer electrolyte precursor solution
[0058] 0.4 g of poly(vinylidene fluoride-hexafluoropropylene) copolymer, 0.1 g of polyvinylidene fluoride and 0.1 g of organic montmorillonite were dissolved in an organic solvent, N,N-dimethylformamide, respectively, stirred evenly at room temperature, and the stirred solutions were mixed;
[0059] 2. Preparation of polymer electrolyte precursor monomer
[0060] Add 5.4 g of methyl methacrylate and 1 g of lithium salt to the uniform solution obtained in step 1, and stir at room temperature to obtain a uniform light yellow solution;
[0061] 3. Polymerization of polymer electrolyte precursor monomers
[0062] Add an initiator to the light yellow solution of step 2, and prepolymerize for 30 minutes under heating conditions to obtain a precursor solution;
[0063] 4. Preparation of polymer electrolyte for all-solid-state lithium-ion batteries
[0064] The precursor solution obtained in step 3 is cast on a glass plate by solution casting, and vacuum dried at 80° C. for 2 h to obtain a light yellow polymer electrolyte film, which is then sliced for later use after being cooled to room temperature;
[0065] 5. Battery Assembly
[0066] The negative electrode shell, the polymer electrolyte film obtained in step 4, the lithium sheet, the nickel foam and the positive electrode shell are assembled in the order of argon gas in a glove box to obtain the high-performance all-solid-state lithium-ion battery.
[0067] The above examples and comparative examples were characterized
[0068] 1) Infrared spectroscopy (FTIR) test. The changes in the functional groups of each component of the polymer electrolyte were tested by infrared spectroscopy (FT-IR, Avatar 370). Before the test, the polymer electrolyte film was cut into pieces, mixed and ground with potassium bromide, pressed into discs and placed in an infrared spectrometer for testing.
[0069] 2) Scanning electron microscope (SEM) test. The surface morphology of the polymer electrolyte was observed by scanning electron microscope (SEM), the instrument model was FEI sirion200, the acceleration voltage was 0.2-30 kV, the resolution was 20 kV, the prepared sample was dried, adhered to the sample holder coated with conductive glue, and tested after gold spraying.
[0070] 3) X-ray diffraction analysis (XRD) test. The effect of the added components on the crystallinity of the polymer electrolyte system was tested by X-ray diffraction analysis (XRD). The instrument model was X'Pert PRO. The parameters were voltage 45 kV, current 40 mA, diffraction angle scanning range 10-90°, scanning speed 5°·s -1 Before testing, the dry sample should be evenly spread on the glass slide and then placed on the sample stage for testing.
[0071] 4) Interface impedance test: Electrochemical impedance spectroscopy was used to test the interface impedance between the polymer electrolyte film and the electrode to determine the stability of the electrolyte-electrode interface. The electrochemical workstation model was CHI760E, with a frequency of 0.01-100000 Hz, and a lithium symmetric battery was assembled for testing.
[0072] 5) Constant current polarization test. The interface stability between the polymer electrolyte and the electrode was tested by constant current polarization. The quality of the interface contact between the polymer electrolyte and the lithium electrode was determined by the voltage-time curve. The instrument model was LAND battery test system CT2001A, and the current density was 0.05 mA cm -2 The battery assembly method is lithium symmetrical battery.
[0073] 6) Charge and discharge test. The charge and discharge test of the battery obtains the charge and discharge specific capacity, charge and discharge efficiency, voltage platform, etc. of the battery during the cycle. The instrument model is LAND battery test system CT2001A, the voltage is set to 2.6V~4.0V, the current rate is 0.5C, and the polymer electrolyte is assembled into a lithium iron phosphate half-cell for testing.
[0074] 7) Cyclic voltammetry test. Cyclic voltammetry is used to determine the battery charge and discharge potential and the stability of the internal redox reaction. The electrochemical workstation model is CHI760E, the test parameters are voltage 2.6V~4.5V, and the scan rate is 0.0005V·s -1 , the test time is 38000s, and the polymer electrolyte is assembled into a lithium iron phosphate half-cell for testing.
[0075] Figure 1 This is the infrared spectrum of the polymer electrolyte prepared by the preparation method of a high-performance all-solid-state lithium-ion battery in Example 1, 1150cm -1 、1240cm -1 and 1729cm -1 The peaks at 1600 cm-1 correspond to the characteristic absorption peaks of CO and C=O in the polymer electrolyte film. -1 The disappearance of the C=C characteristic absorption peak and the appearance of the CO characteristic peak indicate that the methyl methacrylate monomer is successfully polymerized into polymethyl methacrylate in the presence of the initiator benzoyl peroxide.
[0076] Figure 2 The SEM image of the polymer electrolyte prepared by the preparation method of a high-performance all-solid-state lithium-ion battery in Example 1 shows that the polymer electrolyte membrane has a porous structure and a uniform spherical stacking structure, and the pores are dense and uniform, indicating that the three phases of poly(vinylidene fluoride-hexafluoropropylene) copolymer, polyvinylidene fluoride, and polymethyl methacrylate are well dispersed under the action of different surface tensions, and the system is more uniform, which is more conducive to the migration of lithium ions, so that the ionic conductivity reaches σ=1.1×10 -3 S cm -1 , which is 10 times higher than the conductivity of known solid polymer electrolytes in the prior art. -4Left and right (1. F.Zeng,YYSun,B.Hui,YZXia,YHZou,XLZhang,DJYang. ACSApplied Materials And Interfaces, 2020,12(39):43805-43812.2, ZWQiu,C.Liu,J. Wang,JJZhou,Y.Liu,BKGuo,SQShi.ACS SustainableChemistry&Engineering, 2019, 7(11):03158.).
[0077] Compared with the polymer electrolyte of the comparative example, Figure 3 The crystallinity of the polymer electrolyte prepared by the method for preparing a high-performance all-solid-state lithium-ion battery in Example 1 is significantly reduced. The intensity of the diffraction peak at 2θ=20° is reduced, and the shape is similar to the steamed bun peak. The reduction in crystallinity is conducive to ion migration, so that the ion conductivity is greatly improved.
[0078] Figure 4 This is an impedance diagram of a polymer electrolyte prepared by the preparation method of a high-performance all-solid-state lithium-ion battery in Example 1. From the AC impedance of the symmetrical battery, it can be seen that the interface impedance of the embodiment is lower than that of the comparative example, ensuring that the battery has high ionic conductivity and capacity retention.
[0079] Figure 5 The Arrhenius plot of the polymer electrolyte prepared by the preparation method of a high-performance all-solid-state lithium-ion battery in Example 1 shows that the conductivity-temperature curve reflects that the polymer electrolyte shows an amorphous state between 25 and 125°C. Therefore, the polymer electrolyte follows the Arrhenius equation even in the low temperature region. The activation energy of the polymer electrolyte in the example is 14.061 kJ·mol -1 , while the activation energy of the comparative polymer electrolyte is 11.073 kJ·mol -1 Both achieved relatively low activation energies, which are beneficial for lithium ion migration.
[0080] Figure 6 The constant current polarization curve of the all-solid-state lithium-ion battery prepared by the preparation method of a high-performance all-solid-state lithium-ion battery in Example 1 shows that the symmetrical batteries of the two methods can be stably cycled for 200 hours. The polarization curve of the embodiment is smoother, and the polarization voltage (≈0.07V) is much smaller than that of the comparative example (≥0.10V). This shows that the polymer electrolyte of the present invention maintains good contact with the electrode interface, has few side reactions, and has good interface stability.
[0081] Figure 7 This is a rate diagram of an all-solid-state lithium-ion battery prepared by the preparation method of a high-performance all-solid-state lithium-ion battery in Example 1, observing the discharge specific capacity of the battery when cycling at 0.1C, 0.2C, 0.5C, 1C, 2C, 5C and 0.1C. It can be seen from the figure that the discharge specific capacity of the battery at different rates is 154.9 mAh·g -1 、155.6mAh·g -1 、149.7mAh·g -1 、143.1mAh·g -1 、130.9mAh·g -1 、25.3mAh·g -1 and 160.2mAh·g -1 When the cycle returns to 0.1C again, the discharge capacity remains stable and returns to the initial state, indicating that the battery has good cycle stability.
[0082] Figure 8 The cyclic voltammetry curve of the all-solid-state lithium-ion battery prepared by the preparation method of a high-performance all-solid-state lithium-ion battery in Example 1 has an oxidation peak of 3.82 V and a reduction peak of 3.0 V. The overlap of the cyclic voltammetry curves of the five cycles is very high, indicating that the polymer electrolyte in the present invention has good cycle performance.
[0083] Fig. 9 This is the specific capacity-voltage curve of the comparative example cycled at 0.5C. The initial discharge specific capacity is 102.9 mAh g -1 After 100 cycles, the discharge capacity is 47.0 mAh g -1 , the battery capacity decays rapidly during the first 100 cycles and the cycle is unstable.
[0084] Fig.10 This is the efficiency-specific capacity curve of the comparative example cycled at 0.5C. Although the coulombic efficiency of the battery remains basically stable during the cycle, it fluctuates greatly, indicating that the battery has poor cycle stability.
[0085] Fig.11 The specific capacity-voltage curve of the all-solid-state lithium-ion battery cycled at 0.5C prepared by the preparation method of a high-performance all-solid-state lithium-ion battery in Example 1, with an initial discharge specific capacity of 138.8 mAh·g -1 After 100 cycles, the discharge capacity is 147.4 mAh g -1 Compared with the results of the comparative example, the battery of the present invention can be cycled for a long time and maintain a stable charge and discharge specific capacity.
[0086] Fig.12The efficiency-specific capacity curve of the all-solid-state lithium-ion battery at 0.5C prepared by the preparation method of a high-performance all-solid-state lithium-ion battery of Example 1 is shown. During the 100-cycle cycle, the coulomb efficiency is stably maintained at 100%. It is shown that the polymer electrolyte with added azobisisobutyronitrile has better cycle performance than the polymer electrolyte without addition. The solid electrolyte prepared by unpolymerized methyl methacrylate evaporates the methyl methacrylate after vacuum drying and heating, and the matrix solidifies to form a solid electrolyte. However, the assembled battery undergoes structural disintegration after multiple charge and discharge. The reason is that the self-supporting performance of the polymer electrolyte lacking polymethyl methacrylate deteriorates. Under the migration of lithium ions and the action of the electric field, the structure of the electrolyte and the interface first undergoes dynamic evolution, the interface peels off, and the interface impedance surges, resulting in faster attenuation of the charge and discharge specific capacity during the cycle.
Claims
1. A method for preparing a high-performance all-solid-state lithium-ion battery, characterized in that The method is prepared according to the following steps:
1. Pretreatment of polymer electrolyte precursor solution 0.4 g of poly(vinylidene fluoride-hexafluoropropylene) copolymer, 0.1 g of polyvinylidene fluoride and 0.1 g of organic montmorillonite were dissolved in an organic solvent, N,N-dimethylformamide, respectively, and stirred evenly at room temperature, and the stirred solutions were mixed; 2. Preparation of polymer electrolyte precursor monomer Add 5.4 g of methyl methacrylate and 1 g of lithium salt to the uniform solution obtained in step 1, and stir at room temperature to obtain a uniform light yellow solution; 3. Polymerization of polymer electrolyte precursor monomers Add an initiator to the light yellow solution of step 2, and prepolymerize for 30 minutes under heating conditions to obtain a precursor solution; 4. Preparation of polymer electrolyte for all-solid-state lithium-ion batteries The precursor solution obtained in step 3 is cast on a glass plate by solution casting, and vacuum dried at 80° C. for 2 h to obtain a light yellow polymer electrolyte film, which is then sliced for later use after being cooled to room temperature; 5. Battery Assembly The negative electrode shell, the polymer electrolyte film obtained in step 4, the lithium sheet, the nickel foam and the positive electrode shell are assembled in the order of argon gas in a glove box to obtain the high-performance all-solid-state lithium-ion battery; The lithium salt added in step 2 is lithium bis(trifluoromethanesulfonyl)imide; and the initiator in step 3 is benzoyl peroxide.
Citation Information
Patent Citations
All-solid-state polymer electrolyte diaphragm, preparation method and all-solid-state lithium ion battery
CN111799508A
Solid electrolyte membrane, solid lithium ion battery and preparation method of solid lithium ion battery
CN112038692A